Fiscally Informed Total Force Manpower - Thie, Harry J. (RAND Corporation, 2008)
Presents the results of a short-term review of 27 publicly available manpower studies to discover methods that other organizations could use to make "fiscally informed" manpower decisions. The studies exhibit varying methods for determining manpower requirements; however, the method used may not be as important as other attributes, such as the direct involvement of a senior decisionmaker.